2022
DOI: 10.1002/mnfr.202200244
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic Acid Ameliorates High Fat Diet‐Induced Obesity and Insulin Resistance in Mice

Abstract: Scope Insulin resistance is a common feature of obesity and type 2 diabetes and partly results from an imbalance between food intake and energy expenditure. Therefore, efficient and safe insulin resistance treatment therapies are warranted. This work is aim to access the impact of protocatechuic acid (PCA), a catechol‐type O‐diphenol phenolic acid, in high fat diet (HFD)‐induced glucose, and lipid dysregulation. Methods and results Five‐week‐old male C57BL/6 mice are fed with HFD for 4 weeks and then are rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…More than 20 kinds of C3G metabolites (C3G-Ms) in serum have been identified [ 64 ]. Among them, protocatechuic acid [ 65 , 66 , 67 ], vanillic acid [ 68 , 69 ] or their derivatives are the main bioactive metabolites, which have antioxidant and anti-inflammatory activities. The metabolites of C3G detected in this study were protocatechoic acid, methyl 3,4-dihydroxybenzoate, vanillic acid, 4-hydroxybenzeneacetic acid, et al, which may increase C3G bioavailability and contribute to the repair of gut mucosal barrier and intestinal microbiota disorder [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 kinds of C3G metabolites (C3G-Ms) in serum have been identified [ 64 ]. Among them, protocatechuic acid [ 65 , 66 , 67 ], vanillic acid [ 68 , 69 ] or their derivatives are the main bioactive metabolites, which have antioxidant and anti-inflammatory activities. The metabolites of C3G detected in this study were protocatechoic acid, methyl 3,4-dihydroxybenzoate, vanillic acid, 4-hydroxybenzeneacetic acid, et al, which may increase C3G bioavailability and contribute to the repair of gut mucosal barrier and intestinal microbiota disorder [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colectivamente, APCC puede mejorar la resistencia a la insulina hepática y el estado oxidativo vascular mediante la modulación de las vías IRS1/PI3K/AKT2 y AGE-RAGE-NOX4, respectivamente. Xiang et al (2023) Analizaron el impacto del APCC, un ácido fenólico O-difenol de tipo catecol, en la glucosa inducida por una dieta alta en grasas (HFD) y la desregulación de los lípidos. Ellos concluyeron que este estudio proporciona información sobre los potentes efectos farmacológicos del APCC de P á g i n a 9647 fuentes alimenticias para mejorar la resistencia a la insulina en todo el cuerpo inducida por una dieta alta en grasas (HFD) y la diabetes tipo 2.…”
Section: áCido Protocatécuico Y Cáncerunclassified
“…[12][13][14][15] As such, these metabolites might be partially or even wholly responsible for the anti-obesogenic and activating adipose thermogenesis effects of these precursors. [8,9,11] Indeed, two independent groups have recently reported that dietary supplementation with PCA could inhibit HFD-induced obesity in mice and rats, [16,17] and could also increase UCP1 expression in mice. [17] However, the dose of PCA used in these two studies (100 mg kg −1 body weight) is ≈20-fold higher than that produced by gut microbiota transformation of regular human dietary flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9,11] Indeed, two independent groups have recently reported that dietary supplementation with PCA could inhibit HFD-induced obesity in mice and rats, [16,17] and could also increase UCP1 expression in mice. [17] However, the dose of PCA used in these two studies (100 mg kg −1 body weight) is ≈20-fold higher than that produced by gut microbiota transformation of regular human dietary flavonoids. [16][17][18] In other words, these findings may not faithfully reflect the contribution of PCA to its precursor flavonoids effect on obesity and adipose thermogenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation